Efektivitas Model Pakem Dalam Meningkatkan Konsentrasi Belajar Anak Usia Dini - Wijayanti, Wahyu; Efendi, Mukhlison (Institut Agama Islam Negeri Ponorogo, 2021)
Child development, especially the age from birth to entering primary education or the age of 0-8 years is the golden age in the vulnerable human life that cannot be repeated. Therefore this period is the golden age in the vulnerable human life that cannot be repeated. Therefore this period is the right time to lay the foundations for other developments. The objectives of this research are: 1) To find out, to study the planning of the PAKEM learning model in Khairiah Jimbe Islamic Kindergarten Jenangan Ponorogo, 2) Implementation of the PAKEM learning model ini increasing early childhood learning concentration. 3) Knowing and assessing the evaluation of the implementation of the PAKEM learning model in increasing early childhood learning concentration. This research use qualitative research with the type of case study research. The data collected is in the from of primary data and secondary data and data sources come from data sources derived from observations, interviews, and documentation. The data analysis technique follows the concepts put forward by miles and huberman, namely data reduction, data presentation and conclusion drawing. Specifically, it can be described as follows: 1) PAKEM lerning planning is in accordance with Permendikbud Number 146 of 2014 article 2013. 2) The implementation of the PAKEM learning model in increasing the concentration of early childhood learning has been very good, seen from the teacher actively and creatively in teaching and give assignment. 3) The evaluation of learning in increasing the concentration of early childhood learning has been adjusted to the indicators of developmental achievement and refers to the standard of assessment